Sistem Rekomendasi Tempat Pembelian Barang Kerajinan Khas Malang Berbasis Android dengan TOPSIS dan LBS - Kadek Dwi Aryasa; Ratih Kartika Dewi; Adam Hendra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Malang Regency has a diverse culture and has a variety of cultural and historical attractions that can attract visitors. In addition, Malang Regency also has unique handicrafts that have thick East Java artistic value. But craft players feel a lack of special attention from the government. The lack of attention to craft causes little information about handicrafts in Malang to reach visitors. So we need a media that can provide the right place of purchase recommendations with the desired criteria and easy to do. The recommendation place for Purchases of the Malang handicrafts system is using the Waterfall method, android-based, apply Location-Based-Service to get the user position and using TOPSIS to support the decision making because it has a low time complexity and has a light process. The results of Black Box testing are that the system runs well and convenient with the results of the design. In the validation test, it produces results from the system with manual calculations, TOPSIS produces the same results. Finally, the usability test with the SUS method produces the final value of 76.75 which is in the acceptable category and the Good category.